The Silence Before the Big Bang: Joseph Beuys's installation Blitzschlag mit Lichtschein auf Hirsch in the Anthropocene. (2nd July 2020) - Brady, Martin
Abstract : Joseph Beuys's final large-scale installation Blitzschlag mit Lichtschein auf Hirsch (bronze, aluminium, 1958–85) is one of the most viewed works of German art. The four galleries which have it on permanent display (Tate Modern, London; Guggenheim Museum, Bilbao; Museum für moderne Kunst, Frankfurt; Museum of Contemporary Art, North Adams Massachusetts) clock up more than seven million visitors annually. Frequently interpreted following Beuys's death and in the context of the Cold War as an apocalyptic vision, this essay argues that Beuys's environment — a 'landscape' comprising a stag, goat, lightning flash, primordial creatures, and Magnetic North (entitled Boothia Felix ) — should be understood as what Johannes Stüttgen terms a 'future sculpture'. Locating the origins of the components in Beuys's Hirschdenkmäler 'workshop' at the 1982/83 Zeitgeist exhibition in Berlin, the essay examines the absence in Blitzschlag mit Lichtschein auf Hirsch of the ephemeral materials Beuys is commonly associated with: fat, felt, honey, and the like. It is argued that the monumentality and iconography of this installation take it beyond the post-modern 'disintegration of allegory' diagnosed by Peter Bürger in 1987 and make it urgently relevant to contemporary debates about the anthropocene, not least in its proposal of a productive reconciliation between nature and technology.